Hard carbons derived from waste tea bag powder as anodes for sodium ion battery. (29th July 2019) - Arie, Arenst Andreas; Tekin, Burak; Demir, Emrah; Demir-Cakan, Rezan
ABSTRACT: In recent years, biomass-based hard carbons have become main interest in sodium battery research community because of the abundant availability, cheap and excellent electrochemical performance. Here, hard carbons derived from waste tea bag powder have been prepared by hydrothermal carbonization and then followed by the physical activation. The hard carbons possessed sheet-like structures which contained sufficient mesopore and micropore structures to assist the sodium ion transport and electrolyte penetration. The interlayer spacing of the obtained hard carbons is larger than that of graphite which can allow the insertion/extraction of sodium ions during charge-discharge process. When utilized as anodes for sodium ion batteries, the hard carbons performed stable cycle profiles, maintaining a specific capacity of 193 mAh g −1 until the 100 th cycle at a current density of 100 mA g −1 and capacity of 127 mAh g −1 after 200 cycles under a current density of 1000 mA g −1 .